Математичне моделювання динаміки дискретних систем з конкуренцією - Кавалець, Ірина Іванівна (Національний університет "Львівська політехніка", 2013)
У дисертаційній роботі розв’язано актуальну наукову задачу розроблення та аналізу математичних моделей багатоелементних дискретних систем з конкуренцією з нелінійною (ізоеластичною) функцією очікуваних значень вихідних характеристик елементів системи і різними сталими параметрами їх граничної поведінки та методів керування їх нестійкою динамікою. Для розв’язання цієї задачі в роботі проаналізовано відомі математичні моделі систем з конкуренцією та методи керування нестійкою динамікою у таких системах. Побудовано узагальнену модель Курно-Пу з ізоеластичною функцією очікуваних значень вихідних характеристик елементів системи та різними сталими параметрами, що характеризують їх граничну поведінку для багатоелементних дискретних систем з конкуренцією. Розроблено методику дослідження стійкості її точки рівноваги. Обґрунтовано вибір методу керування зі зворотним зв’язком із затримкою (DFC-методу) для контролю нестійкої динаміки системи за допомогою побудованої моделі, а також здійснено його узагальнення. Розроблено математичні моделі керування нестійкою динамікою у двоелементній та триелементній системах з конкуренцією за допомогою DFC-методу. Встановлено умови асимптотичної стійкості точки рівноваги системи при керуванні структурою (вихідною характеристикою) та параметром, що характеризує граничну поведінку елементів системи. Проведено числові експерименти з використанням побудованих моделей для аналізу та керування нестійкою динамікою у багатоелементних дискретних системах з конкуренцією. Наведено аспекти практичного застосування розроблених моделей для аналізу та керування нестійкою динамікою у багатоелементних дискретних системах з конкуренцією. В диссертационной работе решена актуальная научная задача разработки и анализа математических моделей многоэлементных дискретных систем с конкуренцией с нелинейной (изоэластической) функцией ожидаемых значений выходных характеристик элементов системы и различными постоянными параметрами их предельного поведения и методов управления их неустойчивой динамикой. Для решения этой задачи в работе проанализированы известные математические модели систем с конкуренцией и методы управления неустойчивой динамикой в таких системах. Построена обобщенная модель Курно-Пу с изоэластической функцией ожидаемых значений выходных характеристик элементов системы и различными постоянными параметрами, характеризующими их предельное поведение для многоэлементных дискретных систем с конкуренцией. Разработана методика исследования устойчивости ее точки равновесия. Обоснован выбор метода управления с обратной связью с задержкой (DFC-метода) для контроля неустойчивой динамики системы с помощью построенной модели, а также осуществлено его обобщение. Разработаны математические модели управления неустойчивой динамикой в двухэлементных и трехэлементных системах с конкуренцией с помощью DFC-метода. Установлены условия асимптотической устойчивости точки равновесия системы при управлении структурой (выходной характеристикой) и параметром, характеризующим предельное поведение элементов системы. Проведены численные эксперименты с использованием построенных моделей для анализа и управления неустойчивой динамикой в многоэлементных дискретных системах с конкуренцией. Приведены аспекты практического применения разработанных моделей для анализа и управления неустойчивой динамикой в многоэлементных дискретных системах с конкуренцией. Thesis is dedicated to development and analysis of mathematical models of discrete systems with the competition with iso-elastic function of the expected values of the output characteristics and the constant different parameters of the marginal behavior. Methods of control of unstable dynamics are developed and analyzed too. The first chapter is devoted to analysis of the mathematical models of the systems with competition, and the characteristics of such systems are defined. Special attention is paid to examination of historical development of the theory of competition. The basic principles of construction the first models in this direction are defined. The analysis of scientific papers that consider the existence of unstable dynamics in systems with competition and controlling it is carried out. The basic methods of unstable behavior control in different systems, with emphasis on those that apply to systems with the competition are considered. The second chapter describes the basic methods and principles for constructing models of systems with the competition with iso-elastic function of expected values of the output characteristics and the constant different parameters of the marginal behavior. The Cournot-Puu model of two-element system is generalized for the multiple system. Methodology of study the stability of the equilibrium point of the constructed model is proposed. The research of the stability of equilibrium point for two- element and three-element systems is carried out. The third chapter is devoted to the application of control methods, including DFC- method to control unstable state in two-element system with application of Cournot-Puu model. An analysis of asymptotic stability of the equilibrium point in case of control the structure and model’s parameters is conducted. Numerical experiments are carried out. In particular, it is shown how the speed of installation of system to the equilibrium point depends on the values of the output characteristics and feedback factor. Efficient of applying only one control function in the application of the method is substantiated. The fourth chapter considers the application of DFC-method and the Cournot-Puu model to control unstable dynamics in the three-element system. An analysis of the asymptotic stability of the equilibrium point in the case of control structure (linear control), and model’s parameters (nonlinear control) with one and two control functions is carried out. Numerical experiments using DFC-method are done. The generalization of DFC-method for multiple system with the competition with an arbitrary number of control functions is proposed. The practical aspects of applying the developed models to analyze and control the unstable dynamics of multiple discrete systems with competition are shown.
Математическое моделирование динамики дискретных систем с конкуренцией
Mathematical modelling of the dynamics of discrete systems with the competition
Keywords: дискретна система з конкуренцією; динамічний процес; модель Курно-Пу; точка рівноваги; асимптотична стійкість; метод керування зі зворотним зв’язком із затримкою; дискретная система с конкуренцией; динамический процесс; модель Курно-Пу; точка равновесия; асимптотическая устойчивость; метод управления с обратной связью с задержкой; discrete system with the competition; dynamic process; Cournot-Puu model; equilibrium point; asymptotic stability; delayed feedback control method